Ten ways to get a grip on resident co-production within medical education change - Jeffery D. Dagnone (Canadian Medical Education Journal, 2020)
The Royal College of Physicians and Surgeons of Canada (RCPSC) is transforming its national approach to postgraduate medical education by transitioning all specialty programs to competency based medical education (CBME) curriculums over a seven-year period. Queen’s University, with special permission from the RCPSC, launched CBME curricula for all incoming residents across its 29 specialty programs in July 2017. Resident engagement, empowerment, and co-production through this transition has been instrumental in successful implementation of CBME at Queen’s University. This article aims to use our own experience at Queen’s in the context of current literature and rooted in change leadership theory, to provide a guide for educators, learners, and institutions on how to leverage the interest and enthusiasm of trainees in the transition to CBME in postgraduate training. The following ten tips provides a model for avoiding the “black ice” type pitfalls that can arise with learner involvement and ensure a smoother transition for other institutions moving forward with CBME implementation.